Evaluation of the Abnormal Platelet Function in von Willebrand Disease by the Blood Filtration Test - Pareti, Francesco I; Cattaneo, Marco; Carpinelli, Luca; Zighetti, Maddalena L; Bressi, Caterina; Mannuccio Mannucci, Pier; Ruggeri, Zaverio M (Thrombosis and Haemostasis, 1996)
We have evaluated platelet function in different subtypes of von Willebrand disease (vWD) by pushing blood through the capillarysized channels of a glass filter. Patients, including those with type IIB vWD, showed lower than normal platelet retention and increased cumulative number of blood drops passing through the filter as a function of time. In contrast, shear-induced platelet aggregation, measured in the cone-and-plate viscometer, was paradoxically increased in type IIB patients. Treatment with l-desamino-8-D-arginine vasopressin (DDAVP) tended to normalize the filter test in patients with type I-platelet normal and type I-platelet low vWD, but infusion of a factor VUI/von Willebrand factor (vWF) concentrate lacking the largest vWF multimers was without effect in type 3 patients. Experiments with specific monoclonal antibodies demonstrated that the A1 and A3 domains of vWF, as well as the glycoproteins Ibα and Ilb-IIIa on platelets, are required for platelet retention in the filter. Thus, the test may reflect vWF function with regard to both platelet adhesion and aggregation under high shear stress, and provide relevant information on mechanisms involved in primary hemostasis.